Usefulness of Video Head Impulse Test Results in the Identification of Meniere's Disease - Kaci, Brahim; Nooristani, Mujda; Mijovic, Tamara; Maheu, Maxime (Frontiers in Neurology, 2020)
Meniere’s Disease (MD) is an inner ear disorder inducing tinnitus, aural fullness, sensorineural hearing loss and vertigo episodes. In the past few years, efforts have been made to develop objective measures able to distinguish MD from other pathologies. Indeed, some authors investigated electrophysiological measures such as electrocochleography and vestibular evoked myogenic potentials or imaging techniques. More recently the video head impulse test (vHIT) was developed to assess the vestibulo-ocular reflex (VOR). In the last few years, authors aimed at identifying how vHIT may help to identify MD. The objective of this manuscript is to review the different vHIT results in MD patients. We will discuss the usefulness of these findings in the identification of MD, how these results may be explained by pathophysiological mechanisms associated with MD and finally provide directions for future studies.